A new L-type lectin (LvLTLC1) from the shrimp Litopenaeus vannamei facilitates the clearance of Vibrio harveyi. Issue 73 (February 2018) - Tian, Yushun; Chen, Ting; Huang, Wen; Luo, Peng; Huo, Da; Yun, Long; Hu, Chaoqun; Cai, Yiming
Abstract: According to structures and functions of lectins found in shrimp, they are classified into seven types, namely, L-type, C-type, P-type, M-type, galectins, fibrinogen-like domain lectins, and calnexin/calreticulin. Until now, the researches of shrimp lectins are mainly focused on C-type lectins. In this study, we identified a new L-type lectin, designated as Lv LTLC1, from the shrimp Litopenaeus vannamei . The cDNA of Lv LTLC1 is 1184 bp with an open reading frame of 990 bp encoding a protein of 329 amino acids. The Lv LTLC1 protein contained a putative signal peptide, an L-type lectin-like domain, and a transmembrane helix region. Phylogenetic analysis showed that Lv LTLC1 belonged to VIP36-like family. LvLTLC1 was expressed in all examined tissues but had higher expression level in gills and hepatopancreas than other tissues. LvLTLC1 expression was up-regulated after immune challenge by Vibrio harveyi and lipopolysaccharide. The recombinant Lv LTLC1 agglutinated Gram-positive ( Staphylococcus aureus ) and Gram-negative bacteria ( V. harveyi, V. parahaemolyticus, V. alginolyticus, V. cholerae, V. vulnificus, Pseudomonas aeruginosa, P. fluorescens ) in a calcium-independent manner. Recombinant Lv LTLC1 exerted the ability of enhancing the clearance of V. harveyi injected in shrimp. Our results indicated that Lv LTLC1 functions in anti-pathogen innate immunity of shrimp. Highlights: A new L-type lectin ( Lv LTLC1) from the shrimp Litopenaeus vannamei was identified. Lv LTLC1 agglutinates various bacteria in vitro in a calcium-independent manner. Lv LTLC1 enhances the clearance of invading bacteria ( V. harveyi ) in vivo.